Genetic Dissection of Fe-Dependent Signaling in Root Developmental Responses to Phosphate Deficiency. Issue 1 (12th November 2018) - Wang, Xiaoyue; Wang, Zhen; Zheng, Zai; Dong, Jinsong; Song, Li; Sui, Liqian; Nussaume, Laurent; Desnos, Thierry; Liu, Dong
Abstract : Genetic analyses reveal the relationship among the three key molecular components involved in regulating Fe-dependent root developmental responses to phosphate deficiency in Arabidopsis. Abstract: The inhibition of primary root (PR) growth is a major developmental response of Arabidopsis ( Arabidopsis thaliana ) to phosphate (Pi) deficiency. Previous studies have independently uncovered key roles of the LOW PHOSPHATE RESPONSE1 (LPR1) ferroxidase, the tonoplast-localized ALUMINUM SENSITIVE3 (ALS3)/SENSITIVE TO ALUMINUM RHIZOTOXICITY1 (STAR1) transporter complex, and the SENSITIVE TO PROTON RHIZOTOXICITY1 (STOP1; a transcription factor)-ALUMINUM-ACTIVATED MALATE TRANSPORTER1 (ALMT1; a malate transporter) regulatory module in mediating this response by controlling iron (Fe) homeostasis in roots, but how these three components interact to regulate PR growth under Pi deficiency remains unknown. Here, we dissected genetic relationships among these three key components and found that (1) STOP1, ALMT1, and LPR1 act downstream of ALS3/STAR1 in controlling PR growth under Pi deficiency; (2) ALS3/STAR1 inhibits the STOP1-ALMT1 pathway by repressing STOP1 protein accumulation in the nucleus; and (3) STOP1-ALMT1 and LPR1 control PR growth under Pi deficiency in an interdependent manner involving the promotion of malate-dependent Fe accumulation in roots. Furthermore, this malate-mediated Fe accumulation depends on external Pi availability. We also performed a detailed analysis of the dynamic changes in the tissue-specific Fe accumulation patterns in the root tips of plants exposed to Pi deficiency. The results indicate that the degree of inhibition of PR growth induced by Pi deficiency is not linked to the level of Fe accumulated in the root apical meristem or the elongation zone. Our work provides insights into the molecular mechanism that regulates the root developmental response to Pi deficiency.